Child Rights Protection Compliance Ecosystem in Indonesia: Harmonization of the CRC, Digital Risks, Legal Pluralism, and Participation - Muhammad Fachri Said; Syawal Amirul Syah; Andika Prawira Buana; Andi Sri Rezky Wulandari (Greenation Research & Yayasan Global Resarch National, 2026)
This article examined the minimum obligations of the Convention on the Rights of the Child (CRC) can be operationalized in the Indonesian context, which was characterized by legal pluralism and accelerating digital risks. Using normative legal research methods through legislative, conceptual, and limited comparative approaches, this study maps CRC standards and General Comments (particularly GC 5, GC 12, and GC 25) onto national norms, institutional mandates, and implementation-enforcement mechanisms. The findings showed the main problem was not merely a lack of norms, but rather an implementation enforcement gap in the compliance infrastructure: coherence between regimes (child protection, data protection, and platform governance), capacity and coordination across actors, and the absence of auditable procedural indicators to test best interests, protection, and participation. This article proposes a